Effects of electroconvulsive therapy on inflammatory markers and depressive symptoms in adolescents with major depressive disorder - Du, Ning; Wang, Yvna; Geng, Dandan; Chen, Huan; Chen, Fengming; Kuang, Li; Guo, Jiamei (Frontiers in Psychiatry, 2024)
Objective:Limited research exists on the use of electroconvulsive therapy (ECT) for adolescents with major depressive disorder (MDD). This study investigates the effects of ECT on inflammatory markers in adolescents aged 13-18 suffering from severe MDD, evaluating its efficacy in modulating cellular inflammatory markers and ameliorating depressive symptoms. Methods:A cohort of 38 adolescents with severe MDD received standard antidepressant therapy along with 6-8 ECT sessions spanning two weeks. A control group of 29 age-matched, healthy individuals was also assessed for comparative purposes. The investigation measured variations in depressive symptomatology and inflammatory marker levels (IL-1β, IL-6, IL-10) pre- and post-intervention. Results:Post-ECT, a substantial decrease in pro-inflammatory cytokines (IL-1β and IL-6) and an increase in the anti-inflammatory cytokine (IL-10) were noted. Participants who responded to the treatment showed a significant decline in HAMD-17 scores, which accentuates ECT's therapeutic potential. Comparative analysis indicated a significant correlation between post-treatment inflammatory marker alterations and clinical improvement, implying that shifts in inflammatory state might serve as predictors of treatment response. Moreover, the mitigation of depressive symptoms exhibited a moderate correlation with post-treatment decrements in IL-1β and IL-6 levels, underscoring MDD's intricacy and ECT's comprehensive impact. Conclusion:.While initial inflammatory marker levels did not predict the response to ECT, the post-treatment measures appeared to be linked to clinical improvement. These findings suggest ECT's potential effectiveness in treating severe MDD in adolescents and point to the possible predictive value of inflammatory markers in therapeutic outcomes. The study contributes to our understanding of the biopsychosocial framework of MDD and indicates that ECT may be a viable treatment option for this population.